An improved whole-machine balancing method based on double auto-correlation measurement. (February 2018) - Zhang, Zhixin; Zhang, Chuanyi; Wan, Keda; Fu, Yulong; Zhong, Yuebo
The key phase signal is an important factor in the traditional whole-machine balancing method, but, sometimes, it is very hard to get that signal in the rotor system on the scene. A new method to get the unbalance component by only measuring the unbalance vibration amplitude is proposed in this paper. We discuss how to extract the rotor speed based on double auto-correlation; how to identify the unbalance vibration amplitude based on cross-correlation and the design of the special dynamic balancing instrument based on amplitude measurement. This method is also integrated in our newly developed instrument and the experiments prove it works well.